Design of a new self-assembling antioxidant nanomedicine to ameliorate oxidative stress in zebrafish embryos. (15th March 2023) - Shashni, Babita; Tamaoki, Junya; Kobayashi, Makoto; Nagasaki, Yukio
Abstract: Oxidative stress, which is a persistent state of elevated reactive oxygen species (ROS), is implicated in the pathogeneses of several diseases, making antioxidant-based therapeutics the aptest intervention. Nevertheless, the clinical failure of conventional low-molecular-weight (LMW) antioxidants in oxidative stress-related diseases to yield favorable therapeutic outcomes and an increased mortality rate attributable to their poor pharmacokinetic characteristics, necessitates the development of alternative therapeutics. In light of this, we designed and synthesized a new amphiphilic polymer functionalized with a clinically safe base polymer of poly(styrene-co-maleic anhydride) copolymer conjugated with the LMW pleiotropic antioxidant TEMPO (a potent antioxidant) and biocompatible poly(ethylene glycol) (TEMPO-installed PSMA-g-PEG), which self-assembles into nano-sized micelles (SMAPo TN ) under physiological conditions. We investigated its safety and antioxidant ability using zebrafish models. Common LMW antioxidants, such as 4-hydroxy-TEMPO (TEMPOL), vitamin C, N-acetyl-L-cysteine, and edaravone exposure induced phenotypic distortions, a manifestation of developmental toxicity, and resulted in high lethality in zebrafish larvae. LMW TEMPOL also adversely affected embryo hatchability, induced arrhythmia and cardiac edema, and failed to protect against oxidative stress. In contrast, exposure of zebrafish embryos to SMAPo TN increased the hatchability, protected embryos against various inducers of oxidative stress, and did not induce any phenotypic alterations or discernible toxicity. Taken together, we conclude that SMAPo TN surpasses LMW TEMPOL in terms of the ability to protect zebrafish, attributable to efficient ROS scavenging without perturbing normal redox homeostasis. These results imply that SMAPo TN can be used as a therapeutic intervention against various oxidative stress-induced diseases. Statement of significance: Failure of low molecular weight (LMW) antioxidants to improve therapeutic index in various oxidative stress-related pathogenesis, attributable to their poor pharmacokinetic characteristics, greatly limits their clinical translation. To overcome this limitation, we developed a self-assembling antioxidant nanoparticle (SMAPo TN ) comprised of amphiphilic polymer; poly(styrene-co-maleic anhydride) conjugated with TEMPO as an antioxidant and biocompatible poly(ethylene glycol). Preliminary studies carried out in the in vivo models of zebrafish embryos confirmed that exposure of LMW antioxidant resulted in acute developmental toxicity, high lethality, and failure to rescue embryos against oxidative stress inducers. In contrast, SMAPo TN did not exert discernible toxicity and significantly improved their survival under oxidative stress. Our finding establishes antioxidant nanoparticles as more suitable therapeutic intervention for oxidative stress-induced diseases than LMW antioxidants. Graphical abstract: Image, graphical abstract